Line of care for the attention to morbimortality from external causes in adolescents and young people - Mariana Marques; Rosangela Barbiani; Carlise Rigon Dalla Nora; Luiza Cremonese; Taiana Beltrame de Miguel; Rosane Mortari Ciconet; Elson Romeu Farias (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to describe the development and modeling of a line of care for the prevention and attention of morbimortality from external causes in adolescents and young people within the scope of the municipal management of the Unified Health System. Methods: methodological study operationalized in three stages: situational analysis; literature review; development, and modeling. Descriptive statistical analysis and content analysis of the thematic type were used to produce evidence and support the development of the line of care. Results: by upholding the evidence of the study, it was elaborated a line of care, whose theoretical and methodological proposal included: 1) conceptual matrix, 2) educative matrix, 3) assistance matrix, and 4) operative matrix. Final Considerations: the lines of care are strong tools for articulating the levels of health care, being a resolute and feasible proposal given its cost-effectiveness for complex health demands such as the morbimortality of adolescents and young people from external causes.